Genomic and health characteristics of crossbred dairy cattle in central Uganda - Sanchez-Molano, Enrique; Mukiibi, Robert; Riggio, Valentina; Ogwang, Joel; Kawule, Leonard; Benda, Katali; Beine, Peter; de Clare Bronsvoort, Barend M.; Prendergast, James; Doeschl-Wilson, Andrea B.; Muwonge, Adrian (Frontiers in Genetics, 2025)
Introduction:In Africa, dairy cattle contribute significantly to the economy; however, a substantial proportion of these animals are low-yielding indigenous breeds. To increase dairy productivity, crossbreeding with exotic breeds such as European Holstein and Jersey is becoming increasingly common. Uncontrolled crossbreeding practices, however, pose a risk to the genetic integrity of local breeds, as highly productive but potentially maladapted animals may replace indigenous populations. This study aimed to characterise the genetic structure of crossbred dairy cattle in UgandaMethods:We used admixture analysis, while also assessing genomic diversity and inbreeding levels. Additionally, we evaluated the utility of farmer-generated phenotypic databases by integrating them with genomic data to explore the impact of exotic breed crossbreeding on disease frequency.Results and discussion:Findings from this study show a strong influence of exotic breeds (e.g., Holstein) in Ugandan crossbred cattle, leading to lower inbreeding and observed homozygosity than those observed for indigenous breeds. Exploratory analyses of available disease records provided evidence of a strong survivor bias, likely linked to higher mortality rates from diseases such as East Coast fever. These results show the importance of investigating the genetic composition of farm animals, in order to develop informed and sustainable breeding strategies in African dairy cattle systems.